The Development of Hand Gestures Recognition Research: A Review - Aziz, Achmad Noer; Kurniawardhani, Arrie (Universitas Dharma Wacana, 2022)
This paper contains a review of the literature published in the last 5 years that discusses the topic of hand gesture recognition. The focus in this paper leads the reader to see the development of research over the years in hand gesture recognition, in particular that discusses about performance, methods, and datasets used in hand gesture recognition. From this paper, hopefully it can attract researchers’ interest to develop technology more deeply, especially in the field of hand gesture recognition. Hand gestures are not only used as a medium of communication for people with disabilities. Hand gestures can also be used to interact with a computer without any special devices with the technology that is available today.